Development and Characterization of a New Oral Antileishmanial Bis(pyridine-2-Carboxamidine) Drug Through Innovative Dissolution Testing in Biorelevant Media Combined with Pharmacokinetic Studies - Almudena Laguna; Borja Martínez-Alonso; Víctor Guarnizo-Herrero; J. Jonathan Nué-Martinez; Christophe Dardonville; Santiago Torrado-Santiago; Carlos Torrado-Salmerón (Pharmaceutics)
Background/Objectives: Currently there are very few effective oral antileishmanial treatments. In this study we evaluated a new bis(pyridine-2-carboxamidine) antileishmanial drug (JNII40_base) and its hydrochloride salt (JNII40_HCl). Methods: The characterization studies performed allowed us to determine the crystallinity, hydration water, and presence of hydrogen bonds in these drugs. Different dissolution methods were employed to predict intestinal absorption. A high-performance liquid chromatography–mass spectrophotometry (HPLC-MS/MS) method was developed for the determination of JNII40 in plasma. Results: Pharmacokinetic studies in rats of JNII40_base at 100 and 20 mg/kg, and JNII40_HCl at 20 mg/kg, showed a non-linear pharmacokinetic at high doses. An innovative biorelevant medium of phosphate buffer pH 6.8 with polysorbate 80 at 0.6% (w/v) showed high concentration values for JNII40_base at 30 min, which predicts good intestinal absorption. These results were consistent with the bioavailability data, which exhibited a significant (p < 0.05) increase in maximum plasma concentration (Cmax) and a slight delay in time to maximum (Tmax) compared to JNII40_HCl. Furthermore, the sustained release of JNII40_base in this biorelevant media was related to high plasma concentration values at 24 h (C24h) observed in bioavailability studies. These plasma concentrations of JNII40_base were above the half-maximal inhibitory concentration (IC50) against promastigote and amastigote forms of Leishmania donovani, which is indicative of effectiveness and should reduce the occurrence of drug resistance during treatments. Conclusions: The bioavailability and pharmacokinetic data support the consideration of this drug for further in vivo studies as an oral antileishmanial treatment.